Sejarah Pers Perempuan di Sumut (Studi Analisis Wacana Kritis Perspektif Feminis dalam Konten Koran ‘Perempoean Bergerak’ di Sumut) - Lia Anggia Nasution (Universitas Medan Area, 2019)
This study has three main objectives. First, to observe the concept of feminism inside Perempoen Bergerak newspaper’s contents that echoed by journalists in 1919-1920. Second, to observe the working process of Perempoen Bergerak’s redaction “kitchen” as well as the relation of women and men that gave birth to this newspaper. Third, to discover the correlations between Perempoen Bergerak newspaper and women’s movement at that time. This study uses critical discourse analysis method with feminist perspective. The model used in this study is a three-dimensional analysis of Norman Fairlough which illustrates that every event using language is a communicative event consisting of three dimensions namely ; text, discourse practice, and sociocultural practice. Moreover, this study also uses feminist perspective and gender. The researcher found an unequal relationship because men still did not value women equally. The Ethical Political policies imposed by the Dutch at that time greatly influenced the social context of this newspaper. Freedom to taste open education, including freedom to organize, spawns and disseminates ideas for the advancement of women through mass media.